The Role of Social Media on Wardah Cosmetic Users in Bogor City: Product Innovation and Price on Customer Satisfaction - Apriliyanti, Risma; Asmin, Erny Amriani; Gunawan, Rachmat (Universitas KH. Abdul Chalim Mojokerto, 2025)
The stock market is always influenced by various economic and financial factors that determining investor profits. In energy companies, inflation, changes in interest rates, and the company's financial condition, such as profitability, liquidity, and leverage, are important factors that affect stock returns. This study analyzes the influence of these factors on energy companies on the Indonesia Stock Exchange during 2021–2023 and uses multiple linear regression tests. This study found that interest rates and profitability have a significant effect on stock returns, while inflation, liquidity, and leverage do not have a significant effect. These findings indicate that changes in interest rates can have a negative impact on stock returns, while profitability plays a role in determining the level of stock returns. These results indicate that interest rates and profitability need to be considered in investment decisions in the energy sector.